Community delivery of malaria intermittent preventive treatment in pregnancy: protocol of a quasi-experimental evaluation through multistage cluster sampling household surveys in four sub-Saharan African countries. Issue 3 (25th March 2021) - Pons-Duran, Clara; Llach, Mireia; Sanz, Sergi; Ramírez, Máximo; Méndez, Susana; Roman, Elaine; Tholandi, Maya; Pagnoni, Franco; Menendez, Clara; González, Raquel
Abstract : Background: In sub-Saharan Africa (SSA), millions of pregnant women are exposed to malaria infection. The cornerstone of the WHO strategy to prevent malaria in pregnancy in moderate to high-transmission areas is the administration of intermittent preventive treatment (IPTp) with sulfadoxine-pyrimethamine at each scheduled antenatal care (ANC) visit. However, overall coverage remains low. 'Transforming IPT for Optimal Pregnancy' (TIPTOP) project aims at delivering IPTp at the community level (C-IPTp) to complement ANC provision with the goal of increasing IPTp coverage and improving maternal and infant's health. This protocol describes the approach to measure the effect of this strategy through household surveys (HHS) in four SSA countries: Democratic Republic of Congo (DRC), Madagascar, Mozambique and Nigeria. Methods and analysis: A quasi-experimental evaluation has been designed. Delivery of C-IPTp will start first in one area per country, and later it will be extended to two more areas per country. HHS will be carried out before C-IPTp implementation in all study sites, at midterm in initial implementation areas, and after the implementation in all project areas. A multistage cluster sampling method will be followed for the selection of participants. Women of reproductive age who had a pregnancy that ended in the 6 or 12 months prior to the interview, depending on the survey, will be invited to participate by responding to a questionnaire. The main indicators will be coverage of three or more doses of IPTp and attendance to at least four ANC visits. A difference-in-difference analysis will be performed to evaluate the effectiveness of C-IPTp. Ethics and dissemination: The project has been reviewed by the ethics committees of WHO, Hospital Clinic of Barcelona and all project country boards. Project results will be disseminated to in-country stakeholders and at regional and international meetings. TIPTOP project aims to develop and disseminate global recommendations for C-IPTp delivery. Trial registration number: NCT03600844 ; Pre-results.